Generic synthetic inertia scheme for voltage source inverters. Issue 3 (2nd November 2022) - Liang, Jifeng; Fan, Hui; Deng, Zhaoshun; Zhu, Jiebei; Yu, Lujie; Li, Tiecheng; Luo, Peng; Gao, Zeming; Wang, Yajun
Abstract: System kinetic inertia is declining due to the rapid replacement of synchronous generators (SG) by renewable power generations (RPG). To maintain grid inertia, this paper proposes a generic synthetic inertia (GSI) scheme for RPGs, enabling inertial response by a supercapacitor (SC) bank integrated with a voltage source inverter (VSI) DC link via a DC/DC converter. A GSI control loop is developed for the DC/DC converter controller to vary the SC voltage along with the grid frequency for power exchange following the SG swing equation. The GSI scheme realizes plug‐and‐play advantage without modifying the RPG original system. Small‐signal stability analysis is carried out to optimize the GSI controller parameters. The performance of the GSI scheme is evaluated using a modified IEEE 39‐bus test system.